2021
DOI: 10.3389/fbioe.2021.640434
|View full text |Cite
|
Sign up to set email alerts
|

Stress–Strain Index Map: A New Way to Represent Corneal Material Stiffness

Abstract: PurposeTo introduce a new method to map the mechanical stiffness of healthy and keratoconic corneas.MethodsNumerical modeling based on the finite element method was used to carry out inverse analysis of simulated healthy and keratoconic corneas to determine the regional variation of mechanical stiffness across the corneal surface based on established trends in collagen fibril distribution. The Stress–Strain Index (SSI), developed and validated in an earlier study and presented as a parameter that can estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In addition, to eliminate the influence of other factors on corneal biomechanical examination, we observed a new detection index: the SSI. Zhang et al [ 42 ] reported that changes in SSI can be used as an assessment of the effectiveness of treatment in keratoconus. Unlike other stiffness parameters, the change of SSI is not affected by bIOP or CCT and can be used to evaluate the mechanical properties of corneal tissue accurately [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to eliminate the influence of other factors on corneal biomechanical examination, we observed a new detection index: the SSI. Zhang et al [ 42 ] reported that changes in SSI can be used as an assessment of the effectiveness of treatment in keratoconus. Unlike other stiffness parameters, the change of SSI is not affected by bIOP or CCT and can be used to evaluate the mechanical properties of corneal tissue accurately [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approximation, which was necessary due to the lack of complete information on the through-thickness variation in behaviour, could have influenced the model’s outputs. In the numerical modelling used to develop the SSI maps, it was assumed that the areas outside the cone in keratoconic corneas shared the same microstructure as corresponding areas in healthy corneas ( Zhang et al, 2021 ). This assumption was necessary due to the lack of methods to measure corneal microstructure in vivo and was based on evidence from two earlier studies ( Boote et al, 2003 ; Zhou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first study reported only small inter-individual variations in collagen fibril content in healthy corneas of up to 2.9% ( Zhou et al, 2019 ), and the second reported little variation among individuals in fibril diameter ( Dias and Ziebarth, 2013 ). Another limitation is that the validation of the mapping method relied on comparing the numerically-predicted, SSI-based deformation of the cornea along only the cornea’s principal temporal-nasal meridian to that measured clinically by the Corvis ST ( Zhang et al, 2021 ). Further, the method to relate the fibril density reduction inside the cone with the cone morphology was based on information obtained from only 7 KC corneas ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations